Review of the Solid-State Transformers and an Application of Full Bridge DC/DC Converter - Oğuz ALKUL; Şevki DEMİRBAŞ (Gazi Üniversitesi Fen Bilimleri Dergisi, 2019)
With the increased power to weight ratio, corresponding to the developments in material science, the demand for high frequency transformers (HFT) in air, land, marine and aerospace technologies where the weight is particularly important has increased. Especially, the power converters in which HFTs are used with semiconductor switches (Solid State Transformers – SST) have found wide application area in many applications ranging from electric vehicles to space vehicles, distributed generation and storage network integration. In this study, by reviewing SST topologies, simulation and practical implementation of full-bridge converter performing DC/DC conversion have been realized. Firstly, SSTs have been examined and circuit topologies and usage areas has been analyzed in the study. Then, an SST performing DC/DC conversion has been designed and simulated by using full-bridge converter topology. By selecting the required material for the simulated converter, the prototype has been set up and experimental studies have been completed. After completing the experimental setup for the SST, simulated and experimental results are presented by testing SST under 22kHz switching frequency.